Electrochemical and Spectroelectrochemical Analysis of 4-(4-(5-Phenyl-1,3,4-oxadiazole-2-yl)phenoxy)-Substituted Cobalt(II), Lead(II) and Metal-Free Phthalocyanines - KOCA, ATIF (WILEY-V C H VERLAG GMBH, 2015)
Electrochemical and spectroelectrochemical analyses of 4-(4-(5-phenyl-1,3,4-oxadiazole-2-yl)phenoxy)-substituted metal-free phthalocyanine (H2Pc (1)) and metallated phthalocyanines (PbPc (2) and CoPc (3)) were performed in solution. Voltammetric characterizations of the phthalocyanine complexes were investigated by using cyclic voltammetry and square wave voltammetry techniques. CoPc (3) gave common metal and ring based electron transfer reactions; however they split due to the aggregation. Although PbPc (2) illustrated reversible reduction processes during the voltammetric measurements, it was de-metallized and thus turned to the metal free phthalocyanine during repetitive voltammetric cycles and in situ spectroelectrochemical measurements.
Keywords: Electrochemistry; Demetallation; Spectroelectrochemistry; Cyclic voltammetry; Square wave voltammetry; IN-SITU; PHOTODYNAMIC THERAPY; SENSING PROPERTIES; OXYGEN REDUCTION; SOLAR-CELLS; GAS SENSORS; THIN-FILMS; MANGANESE; BEARING; COMPLEXES